PECULIARITIES OF POSTISCHEMIC INFLAMMATORY RESPONSE AT ACUTE LACUNAR STROKES IN ABDOMINALLY OBESE PATIENTS - Delva, M.; Lytvynenko, N. (World of Medicine and Biology, 2012)
Studied the serum levels of the inflammatory interleukins, C-reactive protein, monocyte hemoattractant protein-1 in the 1st and 10th days after lacunar strokes in patients with normal body weight and with abdominal obesity class II. Abdominally obese patients, in comparison with normal body weight patients, have enhanced postischemic inflammatory response during acute lacunar strokes – significant serum increase of C-reactive protein (21,7±5,2 mg/l vs. 7,1±1,4 mg/l, p
Keywords: lacunar strokes; abdominally obese; inflammation